Bicultural Identity and Self/Group Personality Perceptions - Miramontez, Daniel R.; Benet-Martínez, Verónica; Nguyen, Angela-Minhtú D. (Self and identity, 2008)
In two samples of Latino biculturals, we examined the link between bicultural identity integration (BII; degree of compatibility vs. opposition perceived between ethnic and mainstream cultural orientations; Benet-Martínez & Haritatos, 2005 ) and the psychological overlap/distance between the personality traits ascribed to the self, a typical Latino, and a typical Anglo American. As predicted, BII's component of blendedness (vs. distance) was consistently and positively associated with higher overlap between personality ratings of the self and a typical Latino, the self and a typical Anglo American, and a typical Latino and a typical Anglo American. Also as predicted, results with BII's component of harmony (vs. conflict) were not robust. Overall, our results suggest that biculturals with integrated cultural identities have social perceptions of themselves and their cultural in-groups that are closely aligned together, supporting social identity theory.